Upper gastrointestinal endoscopy applied in pediatrics: endoscopic and histological findings, including Helicobacter pylori - Soares Coca, Diego (2018)
Objective: To present and discuss the endoscopic and histological results, as well as the incidence of Helicobacter pylori and other diseases, indications and characteristics of upper digestive endoscopies performed in children. Material and methods: Twenty-five endoscopies were performed in children aged six months to 11 years (mean 7.69 years), from February 2013 to January 2016. In 200 patients, endoscopies were diagnostic and serial biopsies were performed (esophagus, stomach and duodenum), in 120 of them. Results: The indication of endoscopy was diagnosed in 88.89% of the patients, and in 26 patients, a therapeutic procedure was performed. The most frequent endoscopic findings were esophagitis in 49 patients, gastritis in 84 and duodenitis in 16 patients. Four duodenal ulcers were diagnosed. In the therapeutic endoscopies, six gastrostomies were performed, 14 foreign body withdrawals, five nasoenteral tube passages and esophageal dilatation. The H. pylori survey was performed by anatomopathological method and was positive in 26 (13%) of the 200 patients in whom it was searched. Conclusion: pediatric endoscopy is an important niche of the digestive endoscopy, where it is important to emphasize the relevance of the institutional structure that performs these procedures, in order to conduct them safely, being able to treat possible and feasible complications.